Culture filtrate proteins from BCG act as adjuvants for cytotoxic T lymphocyte induction - Mizuno, Satoru; Chuma, Yasushi; Shibuya, Yukihiro; Horibata, Shigeo; Baba, Tomoe; Yokokawa, Emi; Matsuo, Kazuhiro (Frontiers in Immunology, 2023)
Mycobacterium bovis bacilli Calmette-Guerin (BCG) is a licensed vaccine against tuberculosis. It requires attenuated live bacteria to be effective, possibly because actively secreted proteins play a critical role in inducing anti-tuberculosis immunity. BCG also functions as an effective adjuvant. Moreover, the effects of BCG components as adjuvants are not important as those of attenuated live BCG, which is used in cancer immunotherapy. However, the BCG secreted proteins have not been paid attention in anticancer immunity. To understand mycobacterial secreted proteins' function, we investigate immune responses to BCG culture filtrate proteins (CFP). Here, CFP strongly induce both antigen-specific CD4+ T cells and specific CD8+ T cells, which may be functional cytotoxic T lymphocytes (CTLs). In this study, we clearly demonstrate that CFP acts as an adjuvant for CTL induction against specific co-administered proteins and propose CFP as a new protein adjuvant. The CTL response shows potent anticancer effects in mice. These findings could provide insight into the contribution of mycobacterial secreted proteins in both anticancer and antimycobacterial immunity.